(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article examines the theoretical approaches to the theoretical legal foundations of indirect taxes, focuses on the problem of determining the correct ratio of taxes in taxation. A comparative analysis was made in order to determine their optimal ratio. This is because conclusions and proposals have been developed for the purpose of taxation of tax enterprises.